Optimization of accelerated learning technique sport diving students of higher educational institutions - Баламутова Наталя Михайлівна (Natalya Balamutova); Ширяєва Світлана Вікторівна (Svetlana Shyryaeva) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: optimizing the learning process engineering sport diving students of higher educational institutions on the basis of experimental detection features changes leading factors in teaching swimming. Material and Methods: the study involved 102 students of higher educational institutions. Kharkov. All subjects were divided into groups: experimental and control. Methods: theoretical analysis and synthesis of data specific scientific and methodological literature, educational tests, methods of functional diagnostics, pedagogical experiment, methods of mathematical statistics. Results: according to the results of peer reviews of sports engineering methods of navigation, the best results achieved experimental group students. Performance analyses of functional tests that assess the cardiovascular and respiratory systems were higher in the experimental group students than the control. Conclusions: developed an innovative system of accelerated learning technique sport diving students, creates favorable conditions for the improvement of physical development and physical fitness, providing a faster increase athletic performance.